Public Accountability through Merit Values on Civil Service Management in Central Java Province - Septiana Dwiputrianti (Iapa Proceedings Conference, 2020)
Data indicates that implementation of the merit system in civil service management is still far from the target achievement, especially for local governments. This paper assesses the implementation of the merit system of ASN management based on 8 (eight) aspects at the Central Java Province, namely: planning; procurement; career development and development of competencies; promotion, mutation, rotation and demotion; performance management; payroll, reward, and discipline; protection; and supporting facilities. The research instrument was developed from national policies. This study found that Central Java has met category III (good implementation) for 5 aspects. However, it reveals there are still 3 (three) aspects that haven’t met the criteria for good implementation. There are some impediments for implementation in career development, promotion and rotation, and performance management aspects. This finding is very important as a basic reference in the policy evaluation and supporting the bureaucratic reform performance. The recommendation focuses on the development of talent management and talent pool as one of the Indonesian strategic plans to improve the quality of civil service.